Trädslagsinverkan på markvegetationens utveckling i odlingsförsök med tall och contorta - Nylander, Anna (SLU/Dept. of Forest Ecology and Management, 2008)
In the 1970's it was predicted that in the beginning of the 21st century there would be a timber shortage in Sweden and a large scale introduction of the exotic tree species lodgepole pine started. An introduction of a foreign tree species means a risk of a negative influence on the forests ecosystem. Today, the stands that were established in the 70's are middle-aged and the effect on the forest floor vegetation can be studied. This study is focused on the composition of the field and ground layer vegetation in comparable plantations with Scots pine (Pinus sylvestris (L.)) and lodgepole pine (P. contorta Dougl. ex Loud, var. latifolia Engelm).